The Calculation of Voltage Collapse Point by Introducing Branch Current - Yi Tao; Wang Cheng-min; Xie Ning; Gao Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The solutions of power flow can not be obtained easily near the voltage collapse point because the Jacobian matrix is singular. Through analysis of voltage instability region, find the voltage instability region margin, and that is to find the collapse conditions of static voltage stability. We Form the equation that reflect the voltage collapse conditions and establish the extended power flow equations with the hybrid equations as mentioned above, the static voltage collapse point can be calculated by solving the extended equations. The advantage of this method is that the power flow calculation can be convergence smoothly near the collapse point because of the extended power flow equations when the Jacobian matrix tends to be singular. The convergence can be achievable just because the joining of the equation reflecting the voltage collapse conditions has changed the structure of the Jacobian matrix. The simulation results show that this method is very effective. It can solve the voltage collapse point of single-node instability, two-node instability or even all-node instability at the same time. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4408